Inhibition of the NLRP3 inflammasome can prevent sterile intra-amniotic inflammation, preterm labor/birth, and adverse neonatal outcomes - Gomez-Lopez, Nardhy (Biol Reprod, 2019)
Sterile intra-amniotic inflammation is commonly observed in patients with spontaneous preterm labor, a syndrome that commonly precedes preterm birth, the leading cause of perinatal morbidity and mortality worldwide. However, the mechanisms leading to sterile intra-amniotic inflammation are poorly understood and no treatment exists for this clinical condition. Herein, we investigated whether the alarmin S100B could induce sterile intra-amniotic inflammation by activating the NLRP3 inflammasome, and whether the inhibition of this pathway could prevent preterm labor/birth and adverse neonatal outcomes. We found that the ultrasound-guided intra-amniotic administration of S100B induced a 50% rate of preterm labor/birth and a high rate of neonatal mortality (59.7%) without altering the fetal and placental weights. Using a multiplex cytokine array and immunoblotting, we reported that S100B caused a proinflammatory response in the amniotic cavity and induced the activation of the NLRP3 inflammasome in the fetal membranes, indicated by the upregulation of the NLRP3 protein and increased release of active caspase-1 and mature IL-1β. Inhibition of the NLRP3 inflammasome via the specific inhibitor MCC950 prevented preterm labor/birth by 35.7% and reduced neonatal mortality by 26.7%. Yet, inhibition of the NLRP3 inflammasome at term did not drastically obstruct the physiological process of parturition. In conclusion, the data presented herein indicate that the alarmin S100B can induce sterile intra-amniotic inflammation, preterm labor/birth, and adverse neonatal outcomes by activating the NLRP3 inflammasome, which can be prevented by inhibiting such a pathway. These findings provide evidence that sterile intra-amniotic inflammation could be treated by targeting the NLRP3 inflammasome.